(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the treatment outcomes of intrauterine adhesions (IUA) using hysteroscopic surgery at the National Hospital of Obstetrics and Gynecology from August 2024 to August 2025. Subjects and methods: A cross-sectional descriptive study was conducted on 50 patients with intrauterine adhesions who underwent hysteroscopic surgery at the National Hospital of Obstetrics and Gynecology. Results: Among 50 patients undergoing hysteroscopic treatment for intrauterine adhesions, the 35–39 age group accounted for the highest proportion, with moderate adhesions (involving one-third to two-thirds of the uterine cavity) being predominant. Complete adhesiolysis was achieved in the majority of cases, with clear visualization of both tubal ostia. After three months, most patients showed significant improvement in menstrual patterns and complete resolution of pelvic pain. Among the followed-up patients, several achieved spontaneous pregnancy after treatment. The procedure demonstrated a low rate of surgical complications, including isolated cases of bleeding and uterine perforation. Conclusion: Hysteroscopic adhesiolysis is a safe and effective treatment method, enabling restoration of uterine anatomical structure, significant improvement of menstrual function, and enhancement of fertility potential. Appropriate surgical technique selection and accurate assessment of adhesion severity play a crucial role in optimizing treatment outcomes and minimizing complications.